2017
DOI: 10.1093/humrep/dex281
|View full text |Cite
|
Sign up to set email alerts
|

New permeable cryoprotectant-free vitrification method for native human sperm

Abstract: This study was funded by IVF-Spain Foundation. The authors have no conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 26 publications
1
42
2
1
Order By: Relevance
“…Vitrification has been successfully used in freezing of oocytes and embryos with the benefit of being a quick process that does not require expensive equipment [8]. Furthermore, by directly plunging samples into liquid nitrogen, solidification of living cells is achieved without intracellular ice crystallization [32]. However, spermatozoa are osmotically fragile cells and cannot withstand the lethal effect of permeable cryoprotectants at high concentrations needed for successful vitrification [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitrification has been successfully used in freezing of oocytes and embryos with the benefit of being a quick process that does not require expensive equipment [8]. Furthermore, by directly plunging samples into liquid nitrogen, solidification of living cells is achieved without intracellular ice crystallization [32]. However, spermatozoa are osmotically fragile cells and cannot withstand the lethal effect of permeable cryoprotectants at high concentrations needed for successful vitrification [22].…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was first described by Isachenko et al [23] for human semen and soon after also for canine sperm vitrification [8]. Recently, studies using human sperm vitrification protocols showed superior results in motility, viability, DNA structure, acrosome and morphology when compared to conventional freezing protocols [11,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published results from the use of the permeable cryoprotectant-free vitrification protocol (Easy-Sperm®, iGLS S.L., Alicante, Spain) on normozoospermic sperm samples have shown improved preservation of sperm structure and function compared to conventional slow freezing. Sperm motility, vitality, DNA integrity, acrosome and cytoskeleton structure were significantly better preserved in vitrified samples [1].…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Recently, the development of a new permeable cryoprotectant-free vitrification protocol (Easysperm®, iGLS S.L., Alicante, Spain) for human spermatozoa provided an enhanced and reliable alternative for sperm cryopreservation [1]. This novel method has been tested in normozoospermic samples rendering better preservation of sperm quality on all the parameters studied (motility, vitality, DNA structure, acrosome reaction, morphology and cytoskeleton) compared to slow freezing [1].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation